Planning the territory of São Paulo state, Brazil, in the Democratic Period: Carvalho Pinto’s Action Plan (1959 – 1963) - Alves, André Augusto De Almeida (International Planning History Society Proceedings, 2016)
The postwar is marked, in Brazil, by initiatives of state planning and modern architecture that reach their apex in President Juscelino Kubitschek's Targets Plan (1956-1961) and its “synthesis-target”, Brasilia. Contemporary of these achievements is the Action Plan promoted by the governor of São Paulo state, Carvalho Pinto (1959-1963). Sharing the developmentist character that marks Brazilian state planning experience at the time, the Action Plan contains extensive physical targets aiming at the integration of the territory in the production process; relying on the broad participation of planners connected to the Économie et Humanisme Movement of the Dominican Father Louis-Joseph Lebret, the plan incorporates cojunctural analyses, methodologies and public policies that combine such investments in infrastructure and agricultural and industrial expansion with investments envisaging the "improvement of man's conditions". This paper focuses on this Paulista episode of state planning, considering the social scene of the period, providing an overview of its contents and evaluating its results. It makes notes on the economic and technological changes that occurred in the postwar period, and on the process of Brazilian industrialization in the 1950s and 1960s; it attends the conjunctural analyses of the Brazilian and Paulista economy made by the plan's authors, which reveal their perception of the economic and social process and inform their planning activity. It describes the planning process since its organization and constitution of its technical staff, to the strategies used in its elaboration. It provides a framework of the Action Plan that considers integrally: budget management techniques, funding sources, physical targets, public policies. It points out the political content of the plan, exploring its possibilities and limits, notably those related to the urban question and the housing question. It covers the political conditions that made planning almost an unanimity in those years, and the reasons that lead to non-institutionalization of the practice and to the discontinuation of the initiative, after the defeat in Carvalho Pinto's successor race and the subsequent outbreak of the civil-military coup (1964-1985). Thus, being considered in its broader dimensions, Carvalho Pinto’s Action Plan reveals the deep marks left by it in the São Paulo state territory.